Economic recovery strategy of sectoral industries post-COVID-19: Input-output model simulations - Firmansyah Firmansyah; Andrian Budi Prasetyo; Shanty Oktavilia; Siti Hilmiati Azyzia; Dita Wahyu Puspita; Albi Boykhair; Fadel Nugraha (Economies, 2023)
The global COVID-19 pandemic has suppressed the economy and people's welfare, including in Indonesia and Central Java Province, as indicated by the weakening of the national economy by -2.06 percent and locally by -2.65 percent in 2020. Although the economy grew by 3.32 percent in 2021, societal welfare remains lower than in 2019, marked by an increase in unemployment and poverty throughout 2019-2021. Furthermore, the threat of COVID-19 including new variants of the virus continues to weigh on the economy, in 2022 and beyond. This study considered an industrial approach to production, based on inter-industrial linkages and policy simulations with input-output analysis. The objectives of this research are to analyze the impact of the COVID-19 pandemic on the economy of Central Java and to formulate an effective economic recovery policy for industry. The results show that the industries affected by the COVID-19 pandemic in Central Java can promote recovery of overall income in economic industry better than the leading industry and the industries with the highest output multipliers, expressed as a proportional increase in final demand for each industry. Meanwhile, the economic recovery strategy of increasing final demand in industries with high output multipliers results in a faster increase in economic output compared with increasing final demand in the affected industries or leading industries.
Keywords: 330; economic recovery; COVID-19 pandemic; input-output; leading industries; industrial linkage